Pollution sources, beneficial uses and management of Batang Arau and Kuranji River in Padang, Indonesia - Aweng Eh Rak; Hong, P.C; H.Hermanshah (2012)
Batang Arau River and Kuranji River in Padang, Indonesia serve as an important source of fresh water supply for the local communities to carry out their daily activities.Agricultural activities depend on the river as the main source for crop irrigation. However, due to the rapid the industriallization and urbanization that took place especially along Batang Arau River has caused intense pollution to the rivers in Padang. Therefore, a field survey was conducted to identify the type of river usage by the local communities, the source of pollution and to understand the current management of Batang Arau River and Kuranji River by the local authorities. The result showed that apart from industrial waste, improper disposal practiced of domestic waste and sewage by the local communities were the main causes of the river pollution. Batang Arau River was intensely polluted by various sources of pollution and has lower river water quality compared to the Kuranji River. River monitoring and management had been carried out by the Environment Impact Management Agency (Badan Pengendalian Dampak Lingkungan,BAPEDALDA)and Department of Water Resources Management (Dinas Pengelolaan Sumber Air,PSDA)of West Sumatera Province. Although enforcement of laws and regulations to protect the rivers had been practised by the local authorities, constant efforts in increasing the awareness of local communities on the importance of river conservation are necessary to ensure the sustainability of the river ecosystem health and the the ecological services provided by the river river.